2002
DOI: 10.1093/emboj/21.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine sulfation is required for agonist recognition by glycoprotein hormone receptors

Abstract: The glycoprotein hormone receptors (thyrotrophin receptor, TSHr; luteinizing hormone/chorionic gonadotrophin receptor, LH/CGr; follicle-stimulating hormone receptor, FSHr) constitute a subfamily of rhodopsin-like G protein-coupled receptors (GPCRs) with a long N-terminal extracellular extension responsible for high-af®nity hormone binding. These ectodomains contain two cysteine clusters¯anking nine leucine-rich repeats (LRR), a motif found in several protein families involved in protein±protein interactions. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
138
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(148 citation statements)
references
References 48 publications
(90 reference statements)
9
138
1
Order By: Relevance
“…The large number of hydrophobic residues creates a low dielectric-constant microenvironment, enhancing Coulomb charge-charge attraction between the FSHR sulfate and FSH R35β aligned on the upper side of the binding pocket, as well as providing a necessary milieu to accommodate the Y335's hydrophobic phenyl ring. Despite the small interaction area at this site, sulfated Y335 is essential for FSHR activation (16,23). In LHR, the equivalently sulfated tyrosine Y331 and its preceding residue D330 have also been determined as the key signaling residues by site-directed mutagenesis (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large number of hydrophobic residues creates a low dielectric-constant microenvironment, enhancing Coulomb charge-charge attraction between the FSHR sulfate and FSH R35β aligned on the upper side of the binding pocket, as well as providing a necessary milieu to accommodate the Y335's hydrophobic phenyl ring. Despite the small interaction area at this site, sulfated Y335 is essential for FSHR activation (16,23). In LHR, the equivalently sulfated tyrosine Y331 and its preceding residue D330 have also been determined as the key signaling residues by site-directed mutagenesis (22).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of this domain, it is difficult to understand how the ligand-binding signal is conveyed to the transmembrane domain, and the observed ligand receptorbinding mode was challenged and an alternative mode was proposed (15). It has also been shown that sulfated tyrosines in the hinge region of GPHRs (including Y335 for FSHR) are required for hormone recognition and signaling (16). How sulfated residues interact with the hormones, and subsequently lead to receptor activation, remains poorly understood.…”
mentioning
confidence: 99%
“…This modification tends to occur in acidic regions of proteins, usually containing multiple tyrosines [9,11] . Several receptors for chemokines and hormones, including CCR5, CXCR3, C3XCR1, and thyroid-stimulating hormone receptor, have been shown to be sulfated on tyrosines in their amino terminal extracellular domains and some of this sulfation is critical for ligand binding [12][13][14][15][16] . Amino-terminal sulfation of tyrosines in the chemotactic receptor for C5a also contributes to formation of the docking site for the C5a anaphylatoxin [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Although TPST1 and 2 in mammals have 65~67% identical amino acid sequences [28], they seem to have different acceptor preferences [31,37]. Evidence indicates that the posttranslational modification by tyrosine sulfation regulates many important protein-protein interactions and modulates binding affinity and specificity [8,10,11,18,24,26,29,[33][34][35][36]. We previously showed that the sulfation of the tyrosine 385 of TSHR by TPST2 is indispensable for the activation of TSH signaling, and grt mice develop hypothyroidism and dwarfism since they are unable to fully respond to TSH.…”
mentioning
confidence: 99%
“…The expression of TPST2 in the reproductive organs raises the possibility of TPST2 having local functions in mice. Interestingly, luteinizing hormone receptor (LHR) and follicle-stimulating hormone receptor (FSHR), which are essential to the female reproductive systems, have been recently reported to be tyrosine-sulfated [4,36] and the tyrosine-sulfated products have been predicted to modify agonist recognition [10]. Several reports have indicated that the deficiency of LHR or FSHR signal cascades causes female infertility, which is characterized by follicular arrest beyond the Graafian follicle and disturbed ovulation [1,23,38,42].…”
mentioning
confidence: 99%